Membentuk Karakter Remaja Islami Yang Berintegritas Melalui Pembelajaran Akidah Akhlak Di Mts Az-Ziro’ah Al-Washliyah Firdaus - Adel Arianti; Nikmah Royani Harahap; Ade Rahman Matondang (Journal of Innovative and Creativity, 2026)
This study aims to describe the implementation of Akidah Akhlak learning at MTs Az-Ziro’ah Al-Washliyah Firdaus, the Islamic character values and integrity instilled through the learning process, as well as the supporting and inhibiting factors in shaping Islamic youth character with integrity. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews with teachers and students, and documentation. The research subjects consisted of the Akidah Akhlak teacher and eighth-grade students. The results of the study show that the implementation of Akidah Akhlak learning is carried out effectively through lectures, discussions, role modeling, and religious activities. The Islamic character values instilled include honesty, trustworthiness, responsibility, politeness, and patience. Integrity values are reflected in students’ consistent behavior that aligns with Islamic principles in both words and actions. Supporting factors in character formation include the exemplary conduct of teachers, a religious school environment, and parental involvement. Inhibiting factors include negative external influences, social media, and limited instructional time. In conclusion, Akidah Akhlak learning plays a strategic role in developing students’ Islamic character and integrity. Continuous and collaborative efforts among teachers, schools, students, and parents are essential in fostering a generation that is not only intellectually capable but also morally and spiritually strong.